Study of Tumor Necrosis Factor -β (Lymphotoxin) and Cell Death Receptor (TNFR-2) in Rhumatiod Arthritis with Type 2 Diabetes Mellitus - Manar Abbas Al-Ameri, Zeinab. M. Al-Rubaei, (Pakistan Journal of Medical & Health Sciences, 2022)
The aimed of this study is to detect diabetes type 2 in rheumatoid arthritis patients early. Thus, this study determine TNF-β, TNFR-2 in rheumatoid arthritis patients with and without diabetic type 2 and compare results with a control group in order to assess their use as biochemical markers for early diagnosis of rheumatoid arthritis. As well as to find a correlation of TNFR-2 with FBS, AST, ALT, ALP and TNF-β in all subjects in the current study. Age ranged from 35 to 55. The study's participants were separated into three groups: (G1) control (30), (G2) rheumatoid arthritis (30), and (G3) rheumatoid arthritis with T2DM (30). In (G2) and (G3), the levels of AST, ALT, and ALP were considerably higher than in (G1). In addition, there was a highly significant increase in (G3) when compared to (G2). The F.B.S results revealed a non-significant increase in (G2) when compared to (G1), but a highly significant increase in (G3) when compared to (G2) and (G1). When compared to control (G1), the mean value of serum TNF-β was found to be significantly higher in (G2) and (G3). In contrast, the mean value of serum TNF-β in G3 was significantly higher than in G2. In comparison to control (G1) , there was a significantly significant rise in TNFR-2 with (G2) and (G3). In addition a significantly substantial increase in (G3) as comparing to (G2) was found. The relationship between TNFR-2 and all parameters was investigated for all groups. For each group, the correlation coefficient was calculated. TNFR-2 was found to have a strong positive or negative connection. In comparison to G1 (control group)., the study found substantial changes (increase or decrease) in TNFR-2 in G2 and G3 (patient groups) .Furthermore, there are substantial changes in G3 findings when compared to G2. These findings suggested that these measures could be employed as biochemical indicators for detecting diabetes patients with rheumatoid arthritis. Furthermore, a substantial positive or negative correlation of TNFR-2 with all parameters for all groups revealed a good linked biomarker with these patients, indicating that the best medicine and therapy will be available.